Comparison of the capability of risk stratification evaluation between two- and three-dimensional speckle-tracking strain in pre-capillary pulmonary hypertension. (December 2019) - Liu, Bing-Yang; Wu, Wei-Chun; Zeng, Qi-Xian; Liu, Zhi-Hong; Niu, Li-Li; Tian, Yue; Luo, Qin; Zhao, Zhi-Hui; Quan, Rui-Lin; Lin, Jing-Ru; Wang, Hao; He, Jian-Guo; et al.
To investigate and compare the value of right ventricular longitudinal strain detected by two-dimensional and three-dimensional speckle-tracking echocardiography in risk stratification evaluation in pre-capillary pulmonary hypertension. We consecutively screened 66 patients diagnosed with pre-capillary pulmonary hypertension in our center. According to the risk assessment recommended by 2015 European Society of Cardiology Guidelines, all participants were classified into low- and intermediate-high-risk group. Two-dimensional and three-dimensional strains were measured using off-line softwares (GE EchoPAC version 201 and TomTec, 4D RV Function 2.0). Fifty-seven pre-capillary pulmonary hypertension patients (average 35 years old, 18 males and 39 females) were finally enrolled in our study, 32 (56.1%) were classified in low-risk group, while 25 (43.9%) were in the intermediate-high-risk group. Clinical data associated with disease severity, such as N-terminal pro-brain natriuretic peptide ( r  = 0.574, P  < 0.001), peak oxygen consumption ( r  = –0.484, P  < 0.001), and 6-min walking distance ( r  = –0.356, P  = 0.008) were significantly correlated with two-dimensional right ventricular longitudinal strain; while the correlations with three-dimensional right ventricular longitudinal strain were weaker. Receiver operating characteristic curves for the detection of intermediate-high risk stratification showed two-dimensional right ventricular longitudinal strain had the best predictive capacity (area under curve, 0.82, 95% CI: 0.71–0.93, P  < 0.001). Univariate and Multivariate Logistic regression analyses identified two-dimensional right ventricular longitudinal strain as an independent predictor (OR: 1.42, 95% CI: 1.18–1.71, P  < 0.001) of intermediate-high risk stratification in this cohort of pre-capillary pulmonary hypertension patients, the predictive capacity retained (OR: 1.45, 95% CI: 1.18–1.78, P  < 0.001) after adjusted by age, gender, and body mass index, while three-dimensional speckle-tracking echocardiography parameters were not. In conclusion, when used for the detection of intermediate-high risk stratification in pre-capillary pulmonary hypertension, two-dimensional right ventricular longitudinal strain was better than three-dimensional right ventricular longitudinal strain.